UiTM TESL trainee teachers’ perceptions on their expectations and its influence towards students’ performance in the English language writing class / Siti Nor Ashikin Hasnan - Hasnan, Siti Nor Ashikin (Faculty of Education, 2014)
Expectations can be defined as inferences that teachers make about future behaviour or academic performance of their students (Good, 1987). The main purpose for this study is to identify UiTM TESL trainee teachers’ perceptions on expectation and its influence towards their students’ performance in the English language writing class. Guided by four research objectives and research questions, this study has employed a survey research design using quantitative and qualitative methods for data gathering and analysis. The first research objective is to investigate the TESL trainee teachers awareness of their expectation in the classroom, second to identify factors affecting the expectation made, third to identify their ways of expressing their expectations in the classroom and lastly, to discover their perceptions on expectation and the influence of their expectations towards students’ performance in L2 writing class. The samples for this study consisted of 60 TESL trainee teachers who had undergone their practicum session in July 2013. From the data analysis, it can be concluded that TESL trainee teachers’ perceptions on teachers’ expectation and its influence towards students’ performance in L2 writing class is positive. Most of them were aware of their expectations and the influence of their expectations towards students’ performance in L2 writing. In general, the findings show positive result in which TESL trainee teachers thought that teachers' expectations could really influence their behaviour as well as could influence the students’ performance in second language writing class.